Sīang sath̨ōn čhāk Wēthī Sāthārana t̨ō Rāingān Pram̄œn Sathānakān Sitthi Manutsayachon nai Prathēt Thai Pī 2544-2546 (Khana Kammakān Sitthi Manutsayachon h̄æng Chāt, 2005)
Seminar reporting on human rights conditions and works on promoting human rights protection in Thailand from 2001 to 2003.